Controlled atmosphere associated with nitric oxide: a new alternative for the preservation of ‘Prata’ bananas - Zanella, Samara Martins; Gularte, Paulo Sérgio; Cerezer, Bernardo; Buss, Marceli; Zanardi, Aquidauana Miqueloto; Steffens, Cristiano André (Revista de Ciências Agroveterinárias, 2024)
The objective of the present work was to evaluate the effect of nitric oxide (NO) application on the postharvest quality of ‘Prata’ bananas during controlled atmosphere (CA) storage. The fruit were separated into bunches and kept in CA microchambers with 2 kPa of O2 plus 4 kPa of CO2, 13 ± 1 °C and 92% ± 2% and relative humidity (RH) for 25 days. The fruit were treated with 0 (control), 20 μL L-1 of NO at the start of storage, 0.5 and 1 μL L-1 of NO applied daily and 1 and 5 μL L-1 applied every five days. After storage, fruit were evaluated at the time of chamber opening and, after six days in room conditions (23 ± 3°C and RH of 65% ± 5%) for skin color, respiratory and ethylene production rates, soluble solids, titratable acidity, flesh firmness and rot incidence. The experimental design was completely randomized. Treatments with application of 20 μL L-1 of NO at the start of storage, 1 μL L-1 of NO applied daily and every five days provided fruits with better quality attributes. The results show that 1 μL L-1 of NO applied daily or every 5 days is more viable for maintaining fruit quality.